In Vitro Susceptibility of Equine-Obtained Isolates of Corynebacterium pseudotuberculosis to Gallium Maltolate and 20 Other Antimicrobial Agents - Norman, T. E. (American Society for Microbiology, 2014)
This study's objective was to determine the in vitro antimicrobial activities of gallium maltolate (GaM) and 20 other antimicrobial agents against clinical equine isolates of Corynebacterium pseudotuberculosis. The growth of cultured isolates was not inhibited by any concentration of GaM. MIC data revealed susceptibility to commonly used antimicrobials.